Public speaking for college and career - Gregory, Hamilton (Random House, 1987)
The first edition of this public speaking text focuses on the career and community applications of speech-making. It aims to give students a thorough grounding in the speech preparation process, offering three separate chapters on the critical steps of organizing and outlining. Updated sample speeches and outlines include annotations to illustrate key concepts. This edition brings a greater emphasis on ethics, audience adaptation, and credibility, plus a fuller treatment of persuasive techniques.